An Investigation on Enhancement of Solubility of 5 Fluorouracil by Applying Complexation Technique- Characterization, Dissolution and Molecular-Modeling Studies - Kavitha K, Srinivasa Rao A, Nalini.C.N (Journal of Applied Pharmaceutical Science, 2013)
The drug 5 fluorouracil is sparingly soluble in water. The aqueous solubility and dissolution rate of 5-fluorouracil can be increased by inclusion complexation with β-cyclodextrin. Molecular-modeling studies support the formation of stable molecular inclusion complexation of 5-fluorouracil with β-cyclodextrin monomer (1:1). Complexes were prepared by physical mixture, kneading, co evaporation and freeze drying methods. Two ratios 1:1 and 1:2 were formulated. These eight complexes were subjected to Phase-solubility study, molecular modeling and dissolution study. The complexes formed were confirmed by DSC studies. Phase solubility profile indicated that the solubility of 5-fluorouracil increased in the presence of β-cyclodextrin monomer. Results obtained by different characterization techniques clearly indicate that the freeze-drying method leads to formation of solid state complexes between 5-fluorouracil and β-cyclodextrin. The complexation of 5-fluorouracil with β-cyclodextrin lends an ample credence for better therapeutic efficacy.
Keywords: 5-fluorouracil, beta cyclodextrin, complexation, pha